A study of children’s health in S. Paulo City (Brazil), 1984-1985: X - Food intake - Szarfarc, Sophia Cornbluth; Monteiro, Carlos Augusto; Meyer, Mauricio; Tudisco, Eliete Salomon; Reis, Isildinha Marques dos (Revista de Saúde Pública, 1988)
As part of a broad epidemiological survey of the health conditions of under-fives, a random sample (n = 305) of children living in S. Paulo city (Brazil) was submitted to a 24-hour dietary recall. The main results were: a) from one year of age, food intake is not sufficiente to cover the energy requirements of a great part of the population; b) among all ages, but particularly in the two first years of life, dietary provision of iron is very far from the recommended requirements; c) at all ages, protein and vitamin A intakes are reasonably good. Those findings are consistent with the clinical and biochemical evaluation of nutritional status, conducted simultaneously by the survey. The social stratification of the families revealed that socioeconomic status exerts greater influence in the energy intake than in the iron intake. Different hypothesis were raised to explain the energy and iron deficiencies. In the case of energy, the basic cause seems to be the low purchasing power of the population which determines poor food availability and insufficient intake. In the case of iron, the same hypothesis seems to be applicable only after two years of age. Before this age, factors related to precocious weaning and to delay in the introduction of good sources of iron are apparently more important.